Inclusive growth in rural Indonesia: exploring the tnteraction between technology and financial inclusion - Shofi Dana, Badara (Faculty of Islamic Economics and Business UIN Salatiga, 2024)
Financial inclusion, as a form of ease in accessing financial services for the community, is key to creating inclusive growth. This research examines financial inclusion and technology in influencing inclusive growth in rural areas of Indonesia. The analytical approach is a Longitudinal Data Panel. The data is sourced from the Indonesia Family Life Survey (IFLS). The results of this study indicate that financial inclusion influences inclusive growth. On the other hand, technology plays an intermediate role between financial inclusion and inclusive growth in rural areas of Indonesia. The government also needs to provide facilities and security to develop technology.